ANALISIS KETERAMPILAN TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPCK) GURU BIOLOGI SMA NEGERI KOTA PEKANBARU - Evi Suryawati '; Firdaus L.N. '; Yosua Hernandez ' (Program Studi Pendidikan Biologi, 2014)
The aim of this study was to describe biology teachers’ Technological PedagogicalContent Knowledge (TPCK) at Public Senior High School in Pekanbaru. This studyheld on November 2013 until March 2014. The sample of this study was 33 biologyteachers at Public Senior High School in Pekanbaru that selected by random samplingtechnique. This study conducted with closed-ended and open-ended questionnaire.The closed-ended questionnaire consists of 35 items and is 7 subdomains. Thesubdomains are Technological Knowledge (TK), Pedagogical Knowledge (PK),Content Knowledge (CK), Technological Pedagogical Knowledge (TPK),Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK)and Technological Pedagogical Content Knowledge (TPCK). The closed-endedquestionnaire items is valid and reliable. Descriptive study was implemented in thisstudy. The result showed that biology teachers’ TK at Public Senior High School inPekanbaru was good enough (M=3,38), PK was good (M=4,05), CK was good(M=3,92), TPK was good (M=3,70), TCK was good (M=3,70), PCK was very good(M=4,26) and TPCK was good (M=3,94). An overall, biology teachers’ TPCK wasgood (M=3,72). That result indicated that biology teacher at Public Senior HighSchool in Pekanbaru could implement their technology knowledge in biologylearning.Keywords: Technological Pedagogical Content Knowledge, Senior High School,Biology Teacher